Non invasive mechanical ventilation at home / Ventilación mecánica no invasiva a domicilio - Betancourt Reyes, Gilberto Lázaro (Revista Cubana de Medicina Intensiva y Emergencias, 2017)
In this article is exposed a topic very useful, frequent and broadly used in numerous countries around the world. It achieves a theoretical reflection of a topic which is still not within reach of our health system. Used in patient with chronic illnesses and during terminal state of their illnesses where instead of demurrages prolonged in hospital, these patients could cohabit with their irreversible ailment in a worthier and more comfortable way in their own homes, surrounded by their relatives and the psychological support that the family toasts together with the basic health team of the community. The scientific society has noticed of the achievements of this ventilation variety at homes, being vastly accepted in all the latitudes, and our country doesn’t escape from this reality.